Income Risk, Borrowing Constraints, and Portfolio Choice - Guiso, Luigi; Jappelli, Tullio; Terlizzese, Daniele (American Economic Review, 1996)
Economic theory suggests that uninsurable income risk and the expectation of future borrowing constraints can reduce the share of risky assets in a household's portfolio. If the utility function exhibits decreasing absolute risk aversion and decreasing prudence, an individual will reduce his exposure to rate of return risks when confronted with other independent risks. If there are transaction costs, the expectation of future borrowing constraints should induce individuals to keep a lower proportion of their wealth in the form of illiquid and risky assets. We find support for these propositions in a cross-section of Italian households